Recent developments and challenges accompanying with wire arc additive manufacturing of Mg alloys: A review. (2021) - Madhuri, Nalla; Jayakumar, V; Sathishkumar, M
Abstract: Magnesium alloys measure up to date category of decomposable biomaterials with identical stiffness to the bone, diminishing the harmful repercussions of stress shielding. However, Mg alloys measure troublesome to 3D printing because of the zenith chemical responsiveness that leads to a combustion risk. Moreover, Mg customary biocompatible alloying parts and low vaporization temperature will increase the problem of print absolute thick structures that balance corrosion and strength necessities. However, wire arc additive manufacturing (WAAM) has proved its proficiency in attaining the production of middling-to-enormous-scale parts. Because of the practicability of economically manufacturing enormous-scale metal parts with comparatively giant deposition rates, important advancement was created within the WAAM method's understanding, similarly because of the mechanical properties and microstructure of the imaginary parts. As WAAM has enlarged, a large variety of materials became related to the method and its applications. This text discusses the rising analysis of WAAM procedures and a summary of fabric properties. Common defects made in WAAM parts exploitation completely different alloys square measure delineate, together with deformation, porosity, and cracking. This paper concludes that the broad applications, techniques of WAAM and gives out several challenges and future scope.